Requirements engineering of e-complaint management system for Teluk Pulai Primary School, Klang Selangor using iterative development / Nor Amarlia Ab Wahab - Ab Wahab, Nor Amarlia (2015)
The ability to manage customer's complaints well is very important to any organization. It helps to maintain a healthy relationship between the organization and its customer and keeps the customer satisfied. Teluk Pulai Primary School in Klang is currently experiencing problems in managing complaints which is they does not have a computerized system that is able to handling with complaints. The objectives of this project focus on identifying a set of requirements for a complaint management system, developing a prototype and validating the software requirements specification (SRS) using a prototype. As the school is unsure of what they want in the system, a requirement engineering technique adapted from iterative development was used in this project. To achieve all the objectives three phases‟ methodology involved in the beginning, the proposed technique provided a preliminary analysis. The next phase, which is planning phase, a set of use cases was identified and the number of iterations was determined and where each iteration was assigned specific use cases. Lastly, during the execution phase, there are three phases included. At each iteration during this phase, a detailed analysis of each use case was developed, a dynamic user interface prototype was created and validated by the school. In addition, during each iteration, the proposed improvements and recommendation was made and fed into the subsequent iterations. The result of analysis and funding of this project had been documented in the Software Requirements Specification (SRS). In the future, the outcome of this project which is the set of requirements that can be used to develop a complaint management system for educational institutions.